Towards 2030: Sustainable Development Goal 9: Industry, Innovation and Infrastructure. A Sociological Perspective - Andrzej Klimczuk; Grzegorz Piotr Gawron; Magdalena Klimczuk-Kochańska; Piotr Toczyski (Frontiers Media, 2025)
This volume addresses the ninth Sustainable Development Goal. It focuses particularly on the challenges and complexities of industrial development after the COVID-19 crisis. Issues covered by the volume include, among others, social and cultural aspects of technology transfer and global diffusion of groundbreaking technologies, supply chains and the global economy, redesign of the transport systems, multi-level, cross-sectoral, and multi-sectoral cooperation of various stakeholders, regional and local bottom-up responses to crises, the advances in the access to digital infrastructures as well as information and communications technologies, and the new ideas and approaches relevant for the fields of technological policy, industrial policy, and innovative policy.
Keywords: F64; O44; P48; Q55; L52; O38; 330; SDG9; environmental regulation; industrial policies; innovation; sustainable industrial development; technology transfer